Meta-analysis of Molteno glaucoma implants and Ahmed glaucoma valves: insights into efficacy and safety for complex glaucoma - Raja, Adarsh; Bhimani, Sunaina; Alim Ur Rahman, Hafsah; Salman, Madiha; Saeed Shaikh, Afrah; Raja, Sandesh; Zafar Sayeed, Bushra; Feroze, Ahsan; Ahmed, Muhammad (Frontiers in Ophthalmology, 2023)
Glaucoma is a leading cause of irreversible blindness globally and for decades, Molteno and Ahmed glaucoma implants, operating on different mechanisms, have been used to treat complicated glaucoma with varying success.To assess the safety and efficacy of Molteno glaucoma implant (MGI) versus Ahmed glaucoma valve (AGV) in patients with complicated glaucoma.We comprehensively searched PubMed, Google Scholar, Cochrane Library and Science Direct) from inception till July 2023 and studies comparing patients with MGI and those with AGV in patients with complicated glaucoma. The primary outcome was intra-ocular pressure reduction at different time intervals. Secondary outcomes included surgical success rate, hypertensive phase, anti-glaucoma medication (AGM) and total complications.In this meta-analysis, four studies were included with a patient population of 257 with refractory, neovascular or advanced uncontrolled glaucoma. Postoperative intra-ocular pressure reduction did not show significant difference between the two groups (MD: -1.34, 95% CI [-2.78, 0.09]). From the secondary outcomes, surgical success rate (RR: 0.88, 95% CI [0.51,1.53]), hypertensive phase (RR: 0.74, 95% CI [0.39,1.40]) were insignificant. Postoperative anti-glaucoma medication (MD: -0.07, 95% CI [-0.79, -0.65] and total complications (RR:1.36, 95% CI [1.07, 1.72]) were significant.No significant difference was observed between the patients with MGI and AGV for the primary outcome. From the secondary outcome, AGV was associated with reduced anti-glaucoma medication use and significantly lowered the complication.